DNA genetic diversity analysis of oil palm (Elaeis guineensis Jacq.) origin using specific primer for oleic acid and SSR primers - Sylvia Bianca Sihombing; Lollie Agustina Putri; Luthfi Aziz Siregar (Jurnal Agroekoteknologi, 2019)
The aim of the research was to analyze genetic diversity of  origin oil palm DNA by using spesific primer for oleic acid and SSR primer. This research  was conducted in Plant Tissue Culture Laboratory, Faculty of Agriculture,  University of Sumatera Utara , from  March to July  2017. A total of  36 origin of oil palm DNA stock samples issued by PT. Socfin Indonesia was identified using specific ILY-2  primer  marker for oleic acid, FR-3300 primer and  FR-1753 primer. The results showed  analysis of phylogenic dendogram using DARwin 6.0.13 spread 36 samples into three main groups. The first group consist of 12 samples, the second groups consist of 19 samples and the third group consist of 2 samples.Keywords: oil palm,ILY-2 Primer, oleic acid, polymerase chain reaction, SSR primer